On Carcinomas and Other Pathological Entities. Issue 7 (2005) - Smith, Barry; Kumar, Anand; Ceusters, Werner; Rosse, Cornelius
Abstract : Tumours, abscesses, cysts, scars and fractures are familiar types of what we shall call pathological continuant entities . The instances of such types exist always in or on anatomical structures, which thereby become transformed into pathological anatomical structures of corresponding types: a fractured tibia, a blistered thumb, a carcinomatous colon. In previous work on biomedical ontologies we showed how the provision of formal definitions for relations such as is_a, part_of and transformation_of can facilitate the integration of such ontologies in ways which have the potential to support new kinds of automated reasoning. We here extend this approach to the treatment of pathologies, focusing especially on those pathological continuant entities which arise when organs become affected by carcinomas.